C.P.A. Problems and Questions in Theory and Auditing (Book). - Hanson, Arthur W. (The Accounting Review, 1939)
Reviews the book "C.P.A. Problems and Questions in Theory and Auditing," by Jacob B.Taylor and Hermann C.Miller.